PEMAKNAAN KESENIAN JARANAN KEPANG DALAM KEBUDAYAAN MASYARAKAT DESA TAPUNG JAYA KECAMATAN TANDUN - Nainggolan, Marissa Yunda Sonata; Yozani, Ringgo Eldapi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Jaran Kepang, a traditional Javanese art still thriving in Tapung Jaya Village, Tandun District, combines dance, traditional music, and spiritual elements often associated with trance phenomena. Over time, this performance has shifted in meaning from a sacred ritual to cultural entertainment, raising the question of how the local community interprets its significance. This study specifically addresses the problem of how Jaran Kepang is culturally interpreted by the people of Tapung Jaya. Using a qualitative ethnographic approach and symbolic interactionism theory developed by Mead and Blumer, data were collected through participatory observation, in-depth interviews, and documentation. The findings reveal that Jaran Kepang holds multiple meanings: for the performers, it represents identity expression and a spiritual medium believed to bring blessings, while for the wider community, it is regarded as cultural heritage that must be preserved despite evolving interpretations. Interactions between performers, shamans, sinden singers, and audiences shape the symbolic dynamics of the performance, demonstrating its role as a living cultural practice. This research is relevant for advancing cultural communication studies and provides practical contributions to sustaining traditional arts amid modernization and globalization. Keywords: Jaran Kepang; symbolic interactionism; cultural meaning; traditional performance; community identity